Development of STEAM-Based Learning Media (STEAMBOOK) for Teaching Ecosystem Concepts to Fifth-Grade Elementary Students - Aini , Nur; Hadiyanto, Hadiyanto; Widowati, Atri (Papanda Publisher, 2025)
This study aimed to develop a STEAM-based learning medium in the form of a Steambook for teaching ecosystem material to fifth-grade elementary school students. The research employed a Research and Development (R&D) methodology utilizing the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to systematically create and validate the instructional material. The study was conducted at SD Negeri 119 Tanjung Jabung Barat during the 2024-2025 academic year, involving needs analysis with 32 students and one teacher, expert validation by three specialists, and practicality testing through small-group (n=6) and large-group (n=26) trials. Data collection employed validation rubrics and practicality questionnaires, analyzed using percentage calculations and thematic content analysis. Results demonstrated that the Steambook achieved high validity scores across media (86%), content (90%), and language (92%) dimensions, with an overall average of 89% categorized as